ANALYSIS OF COMPLICATIONS OF THE SUB-STENT AUGMENTATION - Мария Анатольевна Лиханова; Константин Анатольевич Сиволапов (Медицина в Кузбассе)
The analysis of complications of sub-axillary augmentation on the basis of 564 out-patient records of patients of dental clinics of Novokuznetsk for 5 years (2013-2017), which was carried out sub-axillary augmentation, dental implantation. The patients were divided into three groups: the first group (200 people) – patients who underwent dental implantation, with alveolar crest height of 10 mm or more according to the standard protocol; the second group (254 people) – patients who underwent sub-axillary augmentation with simultaneous implantation at alveolar crest height of 3 to 5 mm in the open type; the third group of patients (110 people) – patients after sub-axillary augmentation with delayed implantation. The distribution of complications in intraoperative, early postoperative and late postoperative periods was analyzed.